Student Reactions to a Faculty Strike - Amos, Maureen; Day, Victor H.; Power, Elizabeth (Canadian Journal of Higher Education, 1993)
Following a three week faculty strike at Dalhousie University in 1988, questionnaires were obtained from 187 students concerning how the strike affected their academic work, emotions and opinions of the university. Results were analyzed separately for first year undergraduates, other undergraduates, and graduate or professional school students. There was much individual variability in reactions, but on average the strike had slightly negative academic and emotional effects but substantial negative effects on opinions about the university. Undergraduate students indicated the most academic disruption, and upper year undergraduates indicated the most negative opinions. There was no correlation, however, between degree of personally experienced academic disruption and degree of negative opinion. Another survey two years after the strike indicated the reestablishment of positive opinions. Implications for ameliorating the effects of a faculty strike are discussed.